The Application of Behavioral Counseling with Positive Techniques Reinforcement to Improve Self-Confidence - Putri Majiatulhibah; I Wayan Tirka; Dewi Arum MWP (Department of Guidance and Counseling, FIP, Undiksha, 2017)
This study was purposed to determine the effectivity of behavioral counseling by positive reinforcement technique to improved self confidence students of eleventh grade class AK C at SMK Negeri 1 Singaraja. One group pretest-posttest designed was used. The sample of this study were eight students which were grouped with purposive sampling. Student’s self confidence were measured by questionnaire. Data were collected then analyzed by descriptive statistics and t-test. The results showed that behavioral counseling with positive reinforcement technique is effective to improved students self confidence, it seen from the analysis output ttest>ttable with significance value 5% (v), it showed that students self confidence were improved. It can be concluded that alternative hipothesis of this study is accepted.